Activity of the fragile X in heterozygous carriers. - Uchida, I A (1982)
Chromosome analyses with conventional stain, Q- and G-banding, and R-banding with 5-bromodeoxyuridine (BrdU) incorporation were performed on the lymphocytes of two sisters who are heterozygous for the fragile X chromosome and clinically diagnosed as slow learners. Two heterozygous relatives with normal intelligence were used as controls. The frequencies of the active fragile X for the "slow" females were 100/129 (77.5%) and 85/120 (70.8%) compared with 40/78 (51.3%) and 10/32 (31.3%) for controls, the difference being highly significant. These observations are consistent with the Lyon hypothesis: activity of the abnormal X could account for the reduction in mental ability of some heterozygous females. Similar to retarded males with the fragile X chromosome, our slow learners had verbal scores that were lower than performance scores.